An Interfacial Study of Au(111) Electrodes in Deep Eutectic Solvents. Issue 14 (1st June 2022) - Zeller, Sven J.; Geng, Tanja; Ceblin, Maximilian U.; Uhl, Matthias; Kuehne, Alexander J. C.; Kibler, Ludwig A.; Jacob, Timo
Abstract: The electrochemical behavior of Au(111) in contact with deep eutectic solvents (DESs) was studied by cyclic voltammetry, electrochemical impedance spectroscopy (EIS), and immersion experiments to determine the potential of zero total charge (pztc). In particular, DESs type III consisting of a choline salt and a hydrogen bond donor (HBD) were investigated. The HBDs urea and ethylene glycol (EG) were chosen since they belong, in combination with choline chloride (ChCl), to the most widely studied systems. A third HBD used in this study was trifluoroacetamide (TFAcA) because of its remarkable freezing point depression. The adsorption of chloride, nitrate, and sulfate anions on Au(111) was investigated using DESs, as the electrochemical behavior of Au(111) in aqueous electrolytes containing these anions were already well studied. For a better understanding of the interactions of ions in DESs with noble metal electrode surfaces, Au(111) in aqueous ChCl was investigated as well. It was shown that anion adsorption on Au(111) in the DESs under consideration was similar to adsorption in the respective dilute aqueous systems. Abstract : Golden : This study presented the investigation of the interface of Au(111) and different DESs. The focus laid on different anion effects and the high concentration ( e. g ., around 7 m for ChCl+EG) of the ions in DESs. The onset for the lifting of the Au(111) reconstructed surface varied in a range of 0.2 to 0.3 V.